Dinamika Harga Beras di Kota Kendari: Analisis Fluktuasi 2015-2023 - Yusriadin Yusriadin; Rahayu Endah Purwanti; Pertiwi Syarni; Normal Bivariant Padangaran; Muhammad Aldin (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Food price stability is one of the essential issues in the direction of government policy. Price uncertainty at the farm level and the guarantee of food price stability at the consumer level are unresolved problems. This study aims to analyze rice price fluctuations in Kendari City from 2015 to 2024. The research was conducted in Kendari City in March - May 2024. The research used secondary data, namely time series data on rice prices in Kendari City from 2015 to 2023. The research data collection technique is a literature study, namely collecting time series data on rice prices in Kendari City sourced from the Central Bureau of Statistics and related agencies. The research variable is the price of rice in Kendari City from 2015 to 2023. Data analysis used to analyze rice price fluctuations in Kendari City is the Coefficient of Variation (CV). The results showed that rice price fluctuations in Kendari City from 2015 to 2023 were low, with a coefficient of variation (CV) of 3%. The highest rice price condition in Kendari City occurred in 2023, which amounted to IDR 13,321 per kilogram. At the same time, the lowest rice price condition occurred in 2015, which amounted to IDR 9,738 per kilogram. Therefore, government policy intervention is needed to stabilize food prices, especially rice in Kendari City.